Houses for All: The Struggle for Social Housing in Vancouver, 1919-50 - Goheen, Peter G. (Labour / Le Travail, 1995)
The article reviews the book, "Houses for All: The Struggle for Social Housing in Vancouver, 1919-1950," by Jill Wade.
Keywords: BOOKS -- Reviews; HOUSES for All: The Struggle for Social Housing in Vancouver 1919-1950 (Book); Nonfiction; Public housing; WADE, Jill